ID: 74. Issue 1 (November 2015) - Dittrich, Anna; Jessica, Pinno; Wundrack, Nicole; Klepsch, Oliver; Bongartz, Hannes; Schaper, Fred
<x xml:space="preserve">Abstract</x> Mammalian target of rapamycin (mTOR) is a central mediator of cellular growth and survival which is potently activated by interleukin 6 (IL-6). However, the molecular mechanisms of IL-6-induced mTOR activation are still poorly understood. mTOR activity is negatively regulated by regulated in development and DNA damage response 1 (REDD1). Expression of REDD1 is induced by cellular stressors such as DNA damaging agents. Stress-induced REDD1 expression facilitates cellular damage repair by temporarily blocking mTOR-induced signaling. However, reduced REDD1 expression has been associated with proliferative diseases such as liver cancer. We show that REDD1 expression is reduced by IL-6. The reduction of REDD1 protein by IL-6 is independent of proteasomal or caspase-mediated degradation of REDD1 but occurs on the level of REDD1 mRNA. IL-6-induced reduction of REDD1 follows the same kinetics as mTOR activation, suggesting that it contributes to IL-6-induced mTOR activation. The decrease in REDD1 expression is independent of phosphatidylinositide-3-kinase (PI3K) and mitogen-activated protein kinase (MAPK) signaling but depends on the expression and activation of signal transducer and activator of transcription 3 (STAT3). Consequently, inhibition of STAT3 blocks IL-6-induced mTOR activation. Of note, beside basal REDD1 expression also stress-induced REDD1 expression is reduced by IL-6 enabling IL-6 to globally interfere in stress-signaling. In summary, we present a novel STAT3-dependent mechanism of both IL-6-induced activation of mTOR and IL-6-dependent reversion of stress-induced inhibition of mTOR (through repression of REDD1 expression) that might contribute to the development of proliferative diseases in inflammatory conditions.